Introduction to the profession of social work : becoming a change agent - Elizabeth A Segal; Gerdes, Karen E; Steiner, Sue (New Delhi Cengage Learning India Pvt. Ltd., 2019)
Social work as a profession; Central concepts and theories; The power of language; Social work value and ethics; Social work Careers; Is social work for you; Choosing social work as a career.
Keywords: Social Work